A Fair or a Minimum Wage? Women Workers, the State, and the Origins of Wage Regulation in Western Canada - Russell, Bob (Labour/Le Travailleur, 1991)
Abstract Patriarchal domination is now, correctly, viewed as a major feature of social organization in pre-capitalist and non-capitalist societies. In capitalist market societies, it has been related to the operant division of labour, the separation of domestic from waged work and the implications that this has for both spheres of activity. Various theoretical approaches have been developed to account for structured gender inequality in the face of supposed labour market impartiality. By examining an explicit case of gender bias, the use of minimum wage laws to regulate the conditions of women workers, the paper offers an evaluation of these approaches, while at the same time bringing the state and relevant political issues back into the analysis of gender.